Communication Strategy of Islamic Religious Education Teachers in the Formation of Morals of Blind Students - Wahyuningsih, Nur Eka; Kahar, M. Iksan; Cikka, Hairuddin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The communication strategy of Islamic Religious Education teachers in the formation of the morals of students with disabilities has a very important role, because the condition of intellectual limitations requires a special approach that adjusts to the abilities and needs of students. Teachers not only function as material presenters, but also as guides, motivators, and role models that can be imitated by students. Through the use of simple language, patient and repeated two-way communication, the use of visual methods and hands-on practice, and the provision of real examples in daily life, teachers are able to instill Islamic moral values more effectively. A personal, compassionate, and consistent approach is the key to success in internalizing morals in students with disabilities. Thus, the right communication strategy of PAI teachers will help shape the religious behavior, independence, and discipline of students with disabilities, as well as foster mutual respect, manners, and responsibility. This shows that the formation of morals is not only determined by the teaching material, but is greatly influenced by the communication pattern of teachers who are humane, patient, and full of example.